Analisis Rasio Profitabilitas dan Rasio Likuiditas pada Perusahaan Umum Daerah Air Minum Kota Makassar - Malikah Sri Muliyani (LP3M INSTITUT KH YAZID KARIMULLAH, 2026)
This study aims to analyze the financial performance of the Makassar City Regional Drinking Water Company based on profitability and liquidity ratios during the 2021–2023 period. This quantitative research uses secondary data obtained from the company’s audited financial statements, analyzed using profitability ratios (Return on Assets, Return on Equity, and Net Profit Margin) and liquidity ratios (Current Ratio, Cash Ratio, and Quick Ratio). The results indicate that profitability ratios fluctuated, with the highest performance recorded in 2022, followed by a decline in 2023, reflecting reduced efficiency in asset and equity utilization. Meanwhile, liquidity ratios consistently showed a liquid condition, indicating the company’s strong ability to meet short-term obligations. This study contributes to the evaluation of financial performance in regionally owned enterprises by providing empirical evidence that can serve as a basis for managerial decision-making and financial policy improvement.